2023
DOI: 10.1021/acs.orglett.3c01191
|View full text |Cite
|
Sign up to set email alerts
|

Photoalkylation/-arylation of ortho-Diketones with Unactivated Organic Halides

Xiao-Yu Wang,
Yong-Qin He,
Yi Zhou
et al.

Abstract: A new method for conducting a reductive alkylation/arylation of 1,2-diketones using visible light and unactivated organic halides is presented in this article. This technique does not require a photocatalyst and employs Et 3 N, a tertiary amine, as a promoter. This amine aids in generating a ketyl radical and an α-aminoalkyl radical, which engages in a C−X bond activation via a halogen atom transfer process (XAT). This approach's success hinges on utilizing Et 3 N as the promoter. This article's mild and strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…On the basis of our preliminary mechanistic studies and previous literature precedents, we propose a tentative mechanism, as shown in Scheme . Initially, in the presence of 390 nm light, the ketone is converted to either photoexcited ketone ( I ) or diradical ( I′ ) intermediate.…”
mentioning
confidence: 58%
“…On the basis of our preliminary mechanistic studies and previous literature precedents, we propose a tentative mechanism, as shown in Scheme . Initially, in the presence of 390 nm light, the ketone is converted to either photoexcited ketone ( I ) or diradical ( I′ ) intermediate.…”
mentioning
confidence: 58%
“…The high BDE values of C–Cl and C–Br bonds in the alkyl substrates were apparently responsible for their low reactivities. 26…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above results, a possible reaction mechanism was proposed (Scheme ). Under the induction of visible light, the direct hydrogen atom transfer (HAT) proceeded from the C4–H of HE to ketone resulting the ketyl radical 7 (path I), ,, which is highly susceptible to ring opening and the formation of a cyclobutyl radical 8 . Afterward, complex 9 was obtained through the addition of radical 8 to alkene 2 .…”
mentioning
confidence: 99%